A descriptive analysis of instructional coaches' data use in science. Issue 2 (3rd April 2017) - Snodgrass Rangel, Virginia; Bell, Elizabeth R.; Monroy, Carlos
ABSTRACT: A key assumption of accountability policies is that educators will use data to improve their instruction. In practice, however, data use is quite hard, and more districts are looking to instructional coaches to support their teachers. The purpose of this descriptive analysis is to examine how instructional coaches in elementary and middle school science across 3 school districts worked with science teachers around data use. Science teachers and instructional coaches were interviewed about their data use practices and preferences. The findings highlight that coaches play diverse roles in supporting teachers, and that teachers' data use practices closely align with coaches' practices and preferences. The discussion concludes with implications for our understanding of data use in specific content areas and for future research.